Incidence and risk factors of retinopathy of prematurity in Goa, India: a report from tertiary care centre - Kossambe, Sarvesh; Joglekar, Shilpa; D'lima, Annely; Silveira, M. P. (International Journal of Contemporary Pediatrics, 2019)
Background: To report the incidence and risk factors leading to the development of retinopathy of prematurity (ROP) from a tertiary care center in the western Indian state of Goa, India. Methods: This was a prospective observational study carried out in a level II neonatal intensive care unit (NICU) for a period of 18 months. Babies born at < 34 weeks’ gestation and having a birth weight of <1500gm were screened for ROP and laser photocoagulation was done for those who developed threshold ROP. Group differences between any ROP and threshold ROP were analysed using the chi-square test. Results: Out of the 244 preterm neonates screened, 37 developed ROP (15.16%), and 14 out of them (5.73%) developed threshold ROP requiring laser photocoagulation. Very low birth weight, prematurity, apnea, anemia, sepsis, respiratory distress syndrome, bronchopulmonary dysplasia, blood transfusions, exchange transfusions and days taken to reach full enteral feeds and regain birth weight were significantly associated with the development of ROP. Conclusions: This is the first report of ROP from Goa where less than 1 in 5 babies developed ROP. This is similar to that reported across the rest of the country. Judicious oxygen use, ventilation strategies, transfusions guidelines, control of sepsis, early enteral feeds and adequate nutrition may help prevent the development of ROP in the future.